2023
DOI: 10.1002/app.54497
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and corrosion resistance study of two‐dimensional mica‐based composite coatings modified with UIO‐66 and polyethyleneimine

Abstract: Numerous challenges arise from metal corrosion, including economic loss, environmental pollution, and safety issues. Epoxy coatings, as a solution to metal corrosion problems, have been widely used worldwide. The improvement of epoxy coating performance is also a major focus of research. In this paper, we employed a hydrothermal method to load UIO‐66 crystals onto a two‐dimensional mica substrate, while simultaneously modifying the surface with polyethyleneimine (PEI) to enhance the compatibility of the filler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…This indicates that superhydrophobic treatment did not alter the internal crystal structure of ZnO, preserving its fundamental form. 30,31 Additionally, upon comparison, it can be observed that SHZnO exhibits some small scattering peaks around 2θ = 22.5°. 12 This may be attributed to the formation of silica dioxide resulting from the hydrolysis of KH-550.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This indicates that superhydrophobic treatment did not alter the internal crystal structure of ZnO, preserving its fundamental form. 30,31 Additionally, upon comparison, it can be observed that SHZnO exhibits some small scattering peaks around 2θ = 22.5°. 12 This may be attributed to the formation of silica dioxide resulting from the hydrolysis of KH-550.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…Due to its excellent properties such as high adhesion, stability, and low volume shrinkage, epoxy resin is becoming a widely used resin worldwide . Especially in metal corrosion prevention, epoxy resin with high adhesion has become an important choice for coating corrosion protection .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation